Keintelektualan pemikiran melayu dalam cerita lipur lara:satu penetian awal berdasarkan perspektif pendekatan pengurusan (intelectual malay minds in folklore: initial investigation from the perspective of management approach) - Ismail, Mohamad Zuber; Abu Hassan, Mohamad Mokhtar; Beden, Sara (Penerbit Universiti Malaysia Terengganu (UMT), 2015)
This paper explores the scientific and intellectual traditions of Malay civilization in the folklore story based on a new approach in the world of literary criticism in Malaysia namely Management Approach that has been highlighted by Mohamad Mokhtar Abu Hassan (2013). Management approach based on the Educational Dimension of the story of the famous folklore as an important medium in the service of ideas and notions in traditional Malay society appears to have the knowledge and intellectual tradition that is integral to the formation of high civilization and excellence. This tradition clearly demonstrates creativity and intellectual minds of the Malay tradition expressed in the narrative text of the review. The importance of Malay civilization to greatness lies not the 'material' contrary to their knowledge of traditional grandeur and height. In summary, this study will show how a literary work can lead the world through narrative dimension of management in education in order to improve the quality of human capital development in the country's administration. In conclusion, the educational perspective displayed very significant to clearly explained the aspects of traditional literary texts thus, this study provides a further contribution to knowledge of literary criticism in Malaysia.